Daytime Sleepiness and Functional Impairment in Alzheimer Disease - Lee, Jung Hie; Bliwise, Donald L.; Ansari, Farzaneh Pour; Goldstein, Felicia C.; Cellar, Janet S.; Lah, James J.; Levey, Allan I. (The American journal of geriatric psychiatry, 2007)
Daytime sleep has been noted to accompany dementing illness and is more pronounced as dementia severity increases. Although acknowledged by caregivers, sleepiness during the daytime is among the least troublesome of sleep behaviors described in Alzheimer Disease (AD) patients. The purpose of this study was to examine whether patient and spouse/caregiver reports of daytime sleepiness in AD were associated with lower functional status in those patients. The authors utilized the Epworth Sleepiness Scale to assess reported daytime sleepiness and a modification of the Lawton and Brody scale to assess functional status in a group of 137 AD patients. The authors also examined typical bedtimes and wakeup times via questionnaire. Higher levels of daytime sleepiness were associated with greater impairments in functional status. These results were independent of level of cognitive impairment, as assessed with Mini-Mental State Exam, and they were also detectable when the authors limited analyses to data reported only by spouse/caregiver. Findings were not associated with medication use. AD patients also had earlier bedtimes and later wake-up times than a comparison group. Even apart from its association with impaired cognition, daytime sleepiness was associated with functional impairment in AD patients. Although daytime sleep may represent a welcome relief for caregivers, its presence may be associated with greater impairment in instrumental activities and may warrant intervention.